Targeted Removal of Axillary Lymph Nodes After Carbon Marking in Patients with Breast Cancer Treated with Primary Chemotherapy - Hartmann, Steffi; Stachs, Angrit; Kühn, Thorsten; de Boniface, Jana; Banys-Paluchowski, Maggie; Reimer, Toralf (Geburtshilfe und Frauenheilkunde, 2021)
In breast cancer patients who have received primary chemotherapy and then no longer have any suspicious lymph nodes clinically and/or on imaging, marking of initially suspicious axillary lymph nodes with targeted removal has recently been discussed and practised both in Germany and internationally as an alternative to complete axillary lymph node dissection. Tattooing of the suspicious lymph nodes with a highly purified carbon suspension is currently being investigated in clinical studies. Compared with other techniques, the advantages of this method are the high rate of intraoperative lymph node detection, avoidance of an immediately preoperative localisation procedure and the low costs. The practical aspects of lymph node tattooing and the current data regarding this method will be described.Die Markierung und gezielte Entfernung initial suspekter axillärer Lymphknoten bei Mammakarzinompatientinnen, die eine primäre Systemtherapie erhalten und anschließend klinisch und/oder bildgebend keine suspekten Lymphknoten mehr aufweisen, wird aktuell sowohl in Deutschland als auch international als Alternative zur kompletten axillären Lymphknotendissektion diskutiert und praktiziert. Hierzu wird derzeit die Tätowierung der suspekten Lymphknoten mit hochgereinigter Kohlenstoffsuspension im Rahmen klinischer Studien untersucht. Im Vergleich zu anderen Techniken sind Vorteile dieser Methode die hohe Detektionsrate des Lymphknotens intraoperativ, der Verzicht auf Lokalisationsverfahren unmittelbar präoperativ und die geringen Kosten. Im Folgenden sollen die praktische Durchführung der Lymphknotentätowierung und die aktuelle Datenlage zu dieser Methode erörtert werden.
Keywords: breast cancer; lymph nodes; carbon marking; primary chemotherapy; targeted axillary dissection; TAD